Ferroptosis and pyroptosis are connected through autophagy: a new perspective of overcoming drug resistance - Peng Zhao; Shuangshuang Yin; Yuling Qiu; Changgang Sun; Haiyang Yu (Molecular Cancer)
Abstract Drug resistance is a common challenge in clinical tumor treatment. A reduction in drug sensitivity of tumor cells is often accompanied by an increase in autophagy levels, leading to autophagy-related resistance. The effectiveness of combining chemotherapy drugs with autophagy inducers/inhibitors has been widely confirmed, but the mechanisms are still unclear. Ferroptosis and pyroptosis can be affected by various types of autophagy. Therefore, ferroptosis and pyroptosis have crosstalk via autophagy, potentially leading to a switch in cell death types under certain conditions. As two forms of inflammatory programmed cell death, ferroptosis and pyroptosis have different effects on inflammation, and the cGAS-STING signaling pathway is also involved. Therefore, it also plays an important role in the progression of some chronic inflammatory diseases. This review discusses the relationship between autophagy, ferroptosis and pyroptosis, and attempts to uncover the reasons behind the evasion of tumor cell death and the nature of drug resistance.